2016
DOI: 10.4314/ahs.v16i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in multidrug-resistant tuberculosis patients with or without human immunodeficiency virus (HIV) infection before commencement of MDR-TB drug regimen

Abstract: Background: Mycobacterium tuberculosis and human immunodeficiency virus (HIV) are known to cause abnormal thyroid function. There is little information on whether HIV infection aggravates alteration of thyroid function in patients with MDR-TB. Objectives: This study was carried out to determine if HIV co-infection alters serum levels of thyroid hormones (T3, T4) and thyroid stimulating hormone (TSH) in patients with MDR-TB patients and to find out the frequency of subclinical thyroid dysfunction before the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…In the current study, 17.3% of MDR-TB patients had subclinical hypothyroidism and 4 (2.5%) had overt hypothyroidism. The study reported by Ige et al in 2016 (7.8%) from Nigeria 26 indicated a lower proportion of subclinical hypothyroidism than our study finding. Moreover, the study reported by Bares et al in 2016 27 showed higher subclinical (40%) and overt (38%) hypothyroidism than this study.…”
Section: Discussioncontrasting
confidence: 72%
“…In the current study, 17.3% of MDR-TB patients had subclinical hypothyroidism and 4 (2.5%) had overt hypothyroidism. The study reported by Ige et al in 2016 (7.8%) from Nigeria 26 indicated a lower proportion of subclinical hypothyroidism than our study finding. Moreover, the study reported by Bares et al in 2016 27 showed higher subclinical (40%) and overt (38%) hypothyroidism than this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Ige OM et al . [ 29 ] study found 4.35%, 7.83%, and 1.74% of patients had sick euthyroid syndrome, subclinical hypothyroidism, and subclinical hyperthyroidism respectively. Dash M et al .…”
Section: Discussionmentioning
confidence: 99%
“…The patients in our series were young in precarious socioeconomic circumstances, in agreement with trends reported. 2,3,8 While thyroid TB was previously found only in young women, 9 HIV infection, affecting men and women equally, is changing this trend.…”
Section: Discussionmentioning
confidence: 97%